Atypical preeclampsia: fetal maternal approach - Zapata, Alberto (2015)
Four patients diagnosed with pregnancy-induced hypertension (PIH) who, in addition to the signs and symptoms of preeclampsia, presented on admission or during handling hemolysis, elevated liver enzymes, thrombocytopenia v (HELLP syndrome) and studied impaired renal function, with full recovery after childbirth. The common clinical manifestations were headache, epigastric pain, epistaxis v bruising. Serial studies of fetal wellbeing and sufactante determination is made. Termination of pregnancy is decided by worsening maternal or fetal condition, or evidence of fetal lung maturity. In all cases caesarean section was performed. No maternal deaths were submitted. All infants suffered due to atypical preeclampsia, apart from the characteristics of prematurity. The most important neonatal complications were gastrointestinal hypomotility, thrombocytopenia, intrauterine growth retardation v perinatal asphyxia. A case of cerebral palsy v another death from severe neonatal respiratory distress was presented. The importance of correct diagnosis of this clinical picture for proper management, in order to improve both maternal and fetal outcome is obvious.